2014
DOI: 10.1371/journal.pone.0104944
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin Alpha-Subunit (INHA) Expression in Adrenocortical Cancer Is Linked to Genetic and Epigenetic INHA Promoter Variation

Abstract: Adrenocortical carcinoma (ACC) is a rare, but highly malignant tumor of unknown origin. Inhibin α-subunit (Inha) knockout mice develop ACCs following gonadectomy. In man, INHA expression varies widely within ACC tissues and its circulating peptide inhibin pro-αC has been described as a novel tumor marker for ACC. We investigated whether genetic and epigenetic changes of the INHA gene in human ACC cause loss or variation of INHA expression. To this end, analyses of INHA sequence, promoter methylation and mRNA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In prostate and adrenocortical cancers reports of both increased and decreased inhibinα levels have been reported 15 , 61 , 62 . In adrenocortical tumors with lower INHA levels, methylation of the INHA promoter was reported to occur at the CpG island within the proximal HRE site that we identified, suggesting potential roles for epigenetic regulation of INHA as well 62 . HIF transcription factors have reduced binding to methylated hypoxia response elements 63 .…”
Section: Discussionmentioning
confidence: 99%
“…In prostate and adrenocortical cancers reports of both increased and decreased inhibinα levels have been reported 15 , 61 , 62 . In adrenocortical tumors with lower INHA levels, methylation of the INHA promoter was reported to occur at the CpG island within the proximal HRE site that we identified, suggesting potential roles for epigenetic regulation of INHA as well 62 . HIF transcription factors have reduced binding to methylated hypoxia response elements 63 .…”
Section: Discussionmentioning
confidence: 99%
“…The generation of IFN-γ is significantly enhanced by antigen-stimulated T cells in physiological concentrations of VIP, and it was reported that the enhancement of IFN-γ secretion was increased up to a maximum of 14-fold for the VIPR2-selective agonist ( 56 ). INHA encoded a member of TGF-beta superfamily of proteins to regulate multiple cellular processes, including cell proliferation, apoptosis, hormone secretion, and immune response ( 57 ). The construction of immune-related-gene-signature prognostic models in LUAD and LUSC would promote individualized treatment and provide potential novel targets for immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate and adrenocortical cancers reports of both increased and decreased inhibinα levels have been reported 15,69,70 . In adrenocortical tumors with lower INHA levels, methylation of the INHA promoter was reported to occur at the CpG island within the proximal HRE site that we identi ed, suggesting potential roles for epigenetic regulation of INHA as well 70 . HIF transcription factors have reduced binding to methylated hypoxia response elements 71 .…”
Section: Discussionmentioning
confidence: 73%